Marketing Leadership in Government - Elder, Edward. author. aut Link
XI, 148 p. 2 illus. in color.
Keywords: ‘A very interesting study of the communication strategies of John Key and Barack Obama, showing both their similarities and their differences. It covers the need for politicians to acknowledge opposing views and show they have listened to the public, even if not ultimately agreeing with them. “ – David Farrar, Former Political Advisor to the Prime Minister of New Zealand ‘The book has two excellent comparative case studies that it uses throughout in Barack Obama and John Key. It's insightful, thoroughly up to date, and suitable for use in classes on comparative politics, political marketing, political management and political communication. Additionally, there are a host of useful insights for practitioners. It's easy to read and engaging, meaning you want to keep reading it until the end. I couldn't put it down. I thought it was fascinating. Highly recommended for general audiences, students, scholars and practitioners. There's truly something for everyone in this wonderful book by this promising scholar.’ – Ken Cosgrove, Associate Professor of Government, Suffolk University, USA This book explores how contemporary governing leaders can overcome the typical trend of losing a public support in power by following more effective communication strategies. It shows how new forms of communication that emphasise acknowledgement and respect for public criticisms and concerns can be used by governing leaders to show the public that they still have the leadership qualities they entered office with, despite the extra challenges that political office presents. The book outlines a new model, The Contemporary Governing Leaders' Communication Model, through which leaders can communicate their positive personal and professional qualities in government. The book illustrates this model in use through the communication of United States President Barack Obama and New Zealand Prime Minister John Key during their first terms in political office. Edward Elder is a recent PhD graduate from Politics and International Relations at the University of Auckland, New Zealand, whose research focuses on political marketing communication. He published a chapter in Political Marketing in the United States (2014) and an article in the Journal of Nonprofit & Public Sector Marketing. .